2021
DOI: 10.3390/ijerph18105195
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Outbreaks of SARS-CoV-2 on Cruise, Navy and Cargo Ships

Abstract: The confined environment of a ship promotes the transmission of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) due to close contact among the population on board. The study aims to provide an overview of outbreaks of SARS-CoV-2 on board of cruise, navy or cargo ships, to identify relevant outbreak management techniques, related problems and to derive recommendations for prevention. Four databases were searched. The study selection included reports about seroprevalences or clinically/labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 78 publications
(317 reference statements)
1
30
0
1
Order By: Relevance
“…However, the news citations included in our search were the top results from the Google News search engine, and therefore some cases or reports could have been missed. Reassuringly, a meta-analysis of the scholarly literature by Kordsmeyer et al, which examined four databases over a shorter duration (January–July 2020) was roughly in line with the observations of our search [ 11 ]. In this study, a total of 37 studies were included, of which 33 reported outbreaks of SARS-CoV-2 on cruise ships (27 of these studies referred to the Diamond Princess).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the news citations included in our search were the top results from the Google News search engine, and therefore some cases or reports could have been missed. Reassuringly, a meta-analysis of the scholarly literature by Kordsmeyer et al, which examined four databases over a shorter duration (January–July 2020) was roughly in line with the observations of our search [ 11 ]. In this study, a total of 37 studies were included, of which 33 reported outbreaks of SARS-CoV-2 on cruise ships (27 of these studies referred to the Diamond Princess).…”
Section: Discussionsupporting
confidence: 81%
“…Previous systematic reviews of the transmission of SARS-CoV-2 and response to COVID-19 outbreaks on cruise ships have been limited to searches of the scholarly literature and, therefore, reported only on a limited number of outbreaks covered in the scientific literature [ 11 ]. Understanding the dynamics of outbreaks on cruise ships and evaluating the non-pharmaceutical interventions that have been successfully or unsuccessfully employed on these ships can inform future prevention research and policies, as well as benefit planning for future outbreaks with similar transmission patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks of SARS-CoV-2 on various types of ships (cargo, navy, cruise ships) and crew numbers (< 50 in cargo ships to > 1000 in cruise ships) have variable attack rates and mortality even in younger populations. 10 An outbreak with the first strain of SARS-CoV- Although the AR of SARS-CoV-2 Delta strain was high among the vaccinated population aboard the vessel (54%), it was much higher (90%) in the unvaccinated population aboard the South Korean Navy ship. 14 With heightened public health measures and infection control practices, we were able to declare the outbreak over in 26 days.…”
Section: Discussionmentioning
confidence: 99%
“…Out of these 1331 (27.85%) confirmed and suspected COVID-19 infected subjects, 23 (1.73%) have been hospitalized, 4 (0.3%) needed intensive care, and one died [ 229 ]. Diamond Princess is a cruise ship that started a cruise on 20 January 2020 with approximately 3700 passengers and crew members, during which an outbreak of 712 COVID-19 infected subjects occurred (19.24%, p < 0.0000001 vs. Theodore Roosevelt), with 36 (5%, p = 0.00003448 vs. Theodore Roosevelt) hospitalized, and 13 (1.83%, p = 0.00001793 vs. Theodore Roosevelt) deaths [ 230 ]. The significant difference in the attack rates, higher in the military ship, is probably related to the tighter available spaces for sleeping in the military ship, compared to the more comfortable cabins of the Diamond Princess, where social distancing and isolation are easier to reach, whereas the higher rates of hospitalization and death in the Diamond Princess is probably related to the military being young and in good health.…”
Section: Vaccine-preventable Infectious Diseasesmentioning
confidence: 99%